verify that each given function is a solution of the
differential equation.
6.′′\:+\:2y′\:−\:3y\:=\:0;\:y\left(t\right)\:=\:e^{−3t}
"y\u2032\u2032\\:+\\:2y\u2032\\:\u2212\\:3y\\:=\\:0;\\:y\\left(t\\right)\\:=\\:e^{\u22123t}"
Replacing "y'" by "D" , "y''" by "D^2" , we get:
"D^2+2D-3=0\\\\\n\\Rightarrow D^2+3D-D-3=0\\\\\n\\Rightarrow D(D+3)-1(D+3)=0\\\\\n\\Rightarrow (D-1)(D+3)=0\\\\\n\\therefore D=1,-3\\\\"
"\\frac{1}{y}\\frac{dy}{dx}=1,-3\\\\\n\\Rightarrow \\frac{dy}{y}=dx; \\frac{dy}{y}=-3dx\\\\"
Integrating both sides, we get:
"ln(y)=x+c,-3x+c"
"\\therefore y=ke^x,ke^{-3x}"
Now verifying the solution:
When "y=ke^x," we get:
"\\frac{dy}{dx}=ke^x,\\frac{d^2y}{dx^2}=ke^x"
Now, substituting, these in the given differential equation, we get:
"y''+2y'-3y=0\\\\\n\\Rightarrow ke^x+2ke^x-3ke^x=0 \\\\\n\\Rightarrow 0=0"
Hence Verified.
When "y=ke^{-3x}" , we get:
"\\frac{dy}{dx}=-3ke^{-3x},\\frac{d^2y}{dx^2}=9ke^{-3x}"
Now, substituting, these in the given differential equation, we get:
"y''+2y'-3y=0\\\\\n\\Rightarrow 9ke^{-3x}-6ke^{-3x}-3ke^{-3x}=0 \\\\\n\\Rightarrow 0=0"
Hence Verified.
Hence, solutions are obtained and verified.
Comments
Leave a comment